The application of team games tournament learning model to improve student critical thinking in science learning class V SDN 3 Kemaduhbatur - Listianingsih, Ani; Sumardjoko, Bambang; Subowo, Arif (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to (1) describe science learning in the classroom, (2) analyze the application of the Team Games Tournament (TGT) learning model in enhancing students' critical thinking in science education, and (3) identify the supporting and inhibiting factors in implementing the TGT model in class V at SDN 3 Kemaduhbatur. Methodology: A qualitative approach was employed, focusing on descriptive data presented in narrative form without numerical analysis. Data collection techniques included observation, interviews, and documentation. Data validity was ensured through triangulation, while data analysis followed Miles and Huberman’s four-step model: data collection, data reduction, data display, and conclusion drawing/verification. Results: The findings indicate that the TGT learning model effectively improves students’ critical thinking in science learning. The model also enhances students’ understanding of material and promotes active participation in classroom activities. The use of relevant learning media supports the model’s success. However, limited time allocation presents a significant challenge in its implementatio. Applications/Originality/Value: This study emphasizes the value of using the Team Games Tournament learning model to foster critical thinking in science education. The insights derived from this research are expected to serve as a reference for educators seeking to improve instructional strategies and cultivate critical thinking skills among elementary students.